Translation and Validation of Urdu Version of Pediatric Quality of Life Inventory Generic Core Scale for Neoplase Children - Manayer Sajid, Shoaib Waqas, Muhammad Tariq, Asifa Javaid, Hafiz Muhammad Asim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To Translate and validate the Urdu version the Pediatric Quality of Life Inventory Generic Core Scale among neoplase children. Methods: The descriptive cross-cultural linguistic validation study in which PedsQL Generic core scale was conducted by following Bombardier, Beaton and Guillemin’s guidelines for cross cultural adaptation. The study was conducted in different phases i.e. translation and validation. The original English version of PedsQL was translated into Urdu by two individuals, one with an Urdu background and the other from a medical background, during the translation phase (T1, T2) (Forward translation). The T3, T4 Versions were then developed by two independent translators (one with an English background and the other with a medical background). The T1, T2, T3, and T4 versions were compared to the original English version and evaluated by a group of multilingual specialists, resulting in the T5-urdu version. Twenty pediatric rehab professionals were given the T5-urdu version to validate. Results: Chronbach’s alpha value of PedsQL of both child and parent reported after translation were 0.986 and 0.987 respectively and after testing on population were 0.956 and 0.910 respectively. P-values showed significant results which are <0.05 in all domains. The inter domain correlations of child and parent reports after translation and testing on population were >0.70 that interpreted good Pearson correlation. The interclass coeffieneint was ranged from 0.541-0.982. Conclusion: The Urdu version of PedsQL Generic Core Scale of Age 8-12 years both child and parent proxy report is valid for neoplase children.